Experimental Study and Numerical Simulation of Seismic Behavior for RC Columns Subjected to Freeze-Thaw Cycles. (7th March 2017) - Qin, Qing; Zheng, Shansuo; Li, Lei; Dong, Liguo; Zhang, Yixin; Ding, Sha
Abstract : Freeze-thaw of concrete is significantly responsible for serious damage to RC buildings, which may result in premature failure with little warning. Therefore, it is necessary to consider the effects of freeze-thaw environment when assessing seismic performance for RC structures. In this study, pseudo-static experiments of four RC columns were conducted in terms of different number of freeze-thaw cycles (FTCs). The results showed that the FTCs had an influence on the bearing capacity, ductility, strength, and stiffness of RC columns. What is more, the simulation results were commonly smaller than the experimental ones when simply assuming that the degrees of freeze-thaw damage for RC components were uniform. Thus, a numerical model considering uneven distribution of freeze-thaw damage was proposed by utilizing the results of Petersen's test for relative dynamic modulus of elasticity (RDME) for different depths of concrete sample and based on Berto's method which was proved to be effective to convert the numbers of FTCs under different freeze-thaw conditions. On the basis of the existing constitutive relations for concrete, four RC columns subjected to different numbers of FTCs were simulated by OpenSees. As a result, the simulation hysteretic curves were in good agreement with the experimental ones.